OPTIMALISASI MARKETING TERHADAP PENINGKATAN HASIL PENJUALAN PADA SPORTS STATION MALL PANAKUKANG MAKASSAR - Mardiana Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2012)
Marketing is the most important part of a business. Marketing is an overall system of activities aimed at business planning, pricing, promoting and distributing goods and services that satisfy the needs of both the buyer's existing and potential buyers.